Patchy Occurrence of Cowpox Virus in Voles from Germany - Fischer, Stefan; Franke, Annika; Imholt, Christian; Gethmann, Jörn; Spierling, Nastasja G.; Jacob, Jens; Hoffmann, Donata; Beer, Martin; Ulrich, Rainer (Vector-Borne and Zoonotic Diseases, 2020)
Cowpox virus (CPXV), genus Orthopoxvirus, family Poxviridae, is a zoonotic pathogen in Eurasian wild rodents. High seroprevalences have been reported previously for vole and murine species in Europe. In contrast, viral DNA was only rarely detected, and very few reservoir-derived CPXV isolates exist. In this study, CPXV DNA and CPXV-reactive antibodies were monitored in wild small mammals for 5 years in four German federal states. Screening of liver tissues of 3966 animals by CPXV real-time PCR (qPCR) revealed five voles of two species positive for CPXV DNA. Two positive bank voles (Myodes glareolus) and two positive common voles (Microtus arvalis) originated from two plots in Baden-Wuerttemberg. One positive bank vole originated from Mecklenburg-Western Pomerania. None of the small mammals from Thuringia and North Rhine-Westphalia was positive in the qPCR. CPXV antigen-based indirect immunofluorescence assays of 654 highly diluted chest cavity fluid samples detected two bank voles and two common voles from the same sites in Baden-Wuerttemberg to be highly seroreactive. Five animals were CPXV DNA positive, and four other animals were orthopoxvirus seropositive. Our study indicates both a very low prevalence and a patchy occurrence of CPXV in common and bank voles and absence in other rodent and shrew species in Germany. The multiple detection of infected voles at one site in Baden-Wuerttemberg and continued detection in a region of Mecklenburg-Western Pomerania classify these regions as potential endemic foci. Cowpox virus (CPXV), family Poxviridae, genus Orthopoxvirus, is a reemerging zoonotic pathogen in Europe (Essbauer et al. 2010). CPXV has a broad host range in Western Eurasia, for example, cats, pet and farm animals, and various zoo animals representing accidental hosts (Essbauer et al. 2010). The transmission to humans is mainly mediated by contact to infected cats, wild rodents, or pet rats (Essbauer et al. 2010, Hoffmann et al. 2015). Contaminated fomites might play an eminent role in the transmission ...